Relationship between Marital Status and Mental Workload with Work Stress for Work From Home Workers - Lydia Elsa Sinta; Endang Dwiyanti (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Since the COVID-19 pandemic, the work culture in Indonesia has changed. Many companies are implementing the Work From Home (WFH) system. This can cause a dilemma for the workforce due to the assumption that home is a place to rest, not to work. The benefits can be felt since the implementation of Work From Home (WFH). However, there are also negative impacts can be felt by the workforce due to disturbances outside of work. Conflicts between families are also common. The purpose of this study is to determine the strong relationship between marital status and mental workload with work stress in Work From Home (WFH) workers. Methods: This study is a survey research and used a cross-sectional study. The sample in this study is total population of workers in the Group of Digital BolaSport Kompas Gramedia Jakarta, which is 20 people. The variables used in this study were marital status, mental workload, and work stress. The data in this study were obtained by filling out questionnaires about individual characteristic (marital status), mental workload, and work stress. Results: Most of the workers have not married status (60%), high mental workload (55%), and medium work stress (55%). The correlation coefficient value between marital status and work stress is 0.373. Meanwhile, between mental workload and work stress it is 0.667. Conclusion: In Work From Home workers, there is a weak relationship between marital status and work stress. Besides that, there is a strong relationship between mental workload and work stress.